Comparing tree swallow dispersal strategies in a continuous mainland environment - Kelly K. Hallinger; Teresa M. Pegan; Michael J. Andersen; Daniel R. Ardia; Amos Belmaker; David Chang van Oordt; Valentina Ferretti; Anna M. Forsman; Jennifer R. Gaul; Paulo E. Llambías; Sophia C. Orzechowski; J. Ryan Shipley; et al. (Ecology, 2026)
Dispersal is one of the most important aspects of animal behavior and can have far‐reaching consequences for organismal ecology and evolution. Despite recent theoretical advances in understanding why individuals within the same population vary in dispersal behavior, relatively few studies have empirically evaluated the long‐term causes and consequences of variable dispersal within natural populations. In this study, we used life history data collected over the course of 16 years to examine fitness outcomes in 867 known‐age female tree swallows breeding in New York, USA, that differed in their dispersal status: “immigrant” females, defined as dispersers that hatched elsewhere, and “local” females, defined as non‐dispersers that hatched within the study site and returned there after migration to breed. We also compared the life history responses of immigrant and local females to natural variation in weather, nest predation risk, and social environment at their breeding site. Local females were more likely to produce fledglings that recruited into the study area as adults. We also found several instances in which dispersal status interacted with an environmental metric to influence relative fitness, and these responses were largely consistent across life history measures. Overall, immigrant females were relatively resilient to variation in their extrinsic environment, while local females were highly sensitive to environmental conditions at the breeding site, performing relatively well when conditions were benign and faring relatively poorly as conditions became more stressful. We found little evidence that distance dispersed within a study site impacted female fitness, suggesting that the dispersal‐associated differences in fitness that we observed operate mostly across broader spatial scales. Future work should undertake the direct and simultaneous measurement of behavior, physiology, and fitness of immigrant and local females across environmental contexts and should seek to understand whether and how context‐dependent fitness variation of dispersers and non‐dispersers scales up to influence larger ecological and evolutionary processes.